Development policy in small countries - Selwyn, Percy; Institute of Development Studies (Brighton, England) (London : Croom Helm in association with the Institute of Development Studies, 1975)
This comprises of papers prepared for a conference on problems of small developing countries organised by the Institute of Development Studies in August 1972 at the Centre for Multi-Racial Studies at the University of West Indies in Barbados.
Includes bibliographical references.
lje 17/05/2018
Loans
Keywords: Economic development; Economic assistance; States, Small